The Effect of Maturity of Government Internal Control System and Capabilities of Government Internal Supervisory Apparatus on the Government Performance Accountability System - WULANDARI, Sri Puspita; DIN, Muhammad; MASRUDDIN, Masruddin; MASDAR, Rahma (Journal of Governance, Taxation and Auditing, 2024)
This study aims to analyze the effect of the maturity of the Government Internal Control System (SPIP) and the capabilities of the Government Internal Supervisory Apparatus (APIP) on the effectiveness of the Government Performance Accountability System (SAKIP). SPIP, as an internal control framework, functions to ensure that the management of state resources is carried out efficiently, effectively, and in accordance with applicable regulations. On the other hand, APIP, as a supervisory apparatus, plays an important role in ensuring that the implementation of government policies and programs runs in accordance with the objectives that have been set, as well as detecting and preventing deviations. This research uses secondary data from Regional Governments in Indonesia from 2018-2023, with a final sample size of 2,046 observations. The results show that the maturity of the government internal control system (SPIP) and the capability of the government internal supervisory apparatus (APIP) have a positive and significant impact on the government performance accountability system. This study suggests the need to strengthen SPIP and improve the capabilities of APIP to ensure better accountability in the government system, which will ultimately contribute to the improvement of public service quality.